Transfer of the Experimental Autoimmune Glaucoma Model from Rats to Mice—New Options to Study Glaucoma Disease - Reinehr, Sabrina (Int J Mol Sci, 2019)
Studies have suggested an involvement of the immune system in glaucoma. Hence, a rat experimental autoimmune glaucoma model (EAG) was developed to investigate the role of the immune response. Here, we transferred this model into mice. Either 0.8 mg/mL of the optic nerve antigen homogenate (ONA; ONA 0.8) or 1.0 mg/mL ONA (ONA 1.0) were injected in 129/Sv mice. Controls received sodium chloride. Before and 6 weeks after immunization, the intraocular pressure (IOP) was measured. At 6 weeks, retinal neurons, glia cells, and synapses were analyzed via immunohistology and quantitative real-time PCR (RT-qPCR). Additionally, optic nerves were examined. The IOP stayed in the normal physiological range throughout the study (p > 0.05). A significant reduction of retinal ganglion cells (RGCs) was noted in both immunized groups (p < 0.001). Remodeling of glutamatergic and GABAergic synapses was seen in ONA 1.0 retinas. Furthermore, both ONA groups revealed optic nerve degeneration and macrogliosis (all: p < 0.001). An increase of activated microglia was noted in ONA retinas and optic nerves (p < 0.05). Both ONA concentrations led to RGC loss and optic nerve degeneration. Therefore, the EAG model was successfully transferred from rats to mice. In further studies, transgenic knockout mice can be used to investigate the pathomechanisms of glaucoma more precisely.